ANALYSIS AND SYNTHESIS OF PARALLEL MANIPULATORS - Constantin BREZEANU; Cătălina ROBU; Păun ANTONESCU (Fiabilitate şi Durabilitate)
Paper presents a new way of the structural - topological analysis for the parallel manipulators, with referring to the calculation of mobility (degree of freedom) of complex mechanisms. The parallel manipulators are complex topological structure, having the joints (as kinematical pairs) of various types. The thirty six formulas known in the literature for mobility calculation are grouped in two categories: those for a quick calculation of mobility from the visual inspection of kinematical schema, and the approaches based on rank of the kinematical constraint equations. For the parallel manipulators we present a new formula for mobility calculation in function of the kinematical chains number, considered as the identical legs.